2021
DOI: 10.1038/s43018-021-00184-x
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic landscape of RAS-driven cancers from biology to therapy

Abstract: NATuRe CANCeRvarious manners in which oncogenic RAS reprograms metabolism, how these adaptations result in tumor-specific metabolic alterations that in turn modulate oncogenic signaling networks 25,26 and how these metabolic changes may be targeted therapeutically. We focus primarily on KRAS, given the wealth of literature on this major oncogenic driver, and note the roles of other isoforms where these are known.Interplay between oncogenic RAS and glucose metabolism. Altered glucose metabolism, for example, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(137 citation statements)
references
References 155 publications
(270 reference statements)
2
135
0
Order By: Relevance
“…Induction of cholesterol biosynthesis by AP1 and others as well as other death promoting pathways such as tumor necrosis factor TNF [ 44 ] by the compounds then may generate unique intracellular conditions that lead to apoptosis. Interestingly, Glutamine depravation in KRAS mutant cancer cells leads to apoptosis [ 45 ]. Reduction in glutamine synthesis by the compound then could also play a critical role in leukemic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of cholesterol biosynthesis by AP1 and others as well as other death promoting pathways such as tumor necrosis factor TNF [ 44 ] by the compounds then may generate unique intracellular conditions that lead to apoptosis. Interestingly, Glutamine depravation in KRAS mutant cancer cells leads to apoptosis [ 45 ]. Reduction in glutamine synthesis by the compound then could also play a critical role in leukemic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nanoparticles with the antidiabetic drug metformin have been shown to be effective in a pancreatic cancer cell population by inhibiting glutamine metabolism [ 13 ]. Other studies have shown that inhibition of metabolic pathways or RAS ptoteins, especially mutant KRAS, could be a new possibility in anticancer therapy [ 57 ].…”
Section: Nano Delivery and Its Application For Cancer Pharmacotherapeutic Managementmentioning
confidence: 99%
“…via elevated levels of Glutathione-S-transferase (GST) and Superoxide Dismutase (SOD) as well as the downregulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB). NRF2 has been implicated in creating chemoresistance and has been linked to RAS driven cancer [ 16 , 17 ]. These effects lead to decreased cytokine secretion and decreased tissue injury resulting in enhanced survival in the murine model of LPS induced endotoxemia [ 109 ].…”
Section: Chitosan-based Nanoformulationsmentioning
confidence: 99%
“…Mice with mutations in the PI3K catalytic subunit p110α that render it unable to bind Ras are highly resistant to oncogenic Ras-induced tumorigenesis [109]. Mutant KRAS also has been shown to abnormally induce activation of mTOR complexes which controls protein synthesis and folate cycle [110]. Another well-described crosstalk route is the inhibitory phosphorylation of RAF by Akt on serine 259, where activated Akt can attenuate RAF and downstream signalling [111][112][113].…”
Section: Crosstalk With the Ras/erk Signalling Pathwaymentioning
confidence: 99%